Study of Impact Factor on Electrokinetic Remediation of Copper Contaminated Soils - Hu, Shuheng; Tong, Junjun; Zhu, Chengzhu; Wang, Jiaquan (Asian Journal of Chemistry, 2014)
The efficiencies of electrokinetic remediation of copper contaminated soils were studied by means of experiments in this paper. The influence of electrolyte, pH value of cathode solution, voltage gradient, remediation time and initial concentration of copper on electrokinetic processes was inspected and migration and variation characteristics of copper were analyzed as well. The results indicated that electrokinetic transport process can promote desorption and migration of copper in soils effectively; and the migratory performance of Cu was related closely to the electrolyte, the effect order was KCl > KNO3 > Na2SO4 > KH2PO4; voltage gradient and experiment time had correlativity with the removal efficiency of copper. The removal efficiency was 83.60 % when voltage gradient was 2 V cm-1, cathode solution of citric acid-sodium citrate buffer pH = 5, electrolyte of KCl and remediation time was 5d.